Prevalence of depression and its associated factors among adolescents in China during the early stage of the COVID-19 outbreak - Han Qi (PeerJ Inc., 2021)
Background The outbreak of the 2019 coronavirus disease outbreak (COVID-19) had a detrimental impact on adolescents’ daily life and studying, which could increase the risk of depression. This study examined the prevalence of depressive symptoms (depression hereafter) among Chinese adolescents and its associated factors. Methods An online survey was conducted during the COVID-19 outbreak in China. Adolescents aged 11–20 years who currently lived in China were invited to participate in the study. Data were collected with the “SurveyStar” platform using the Snowball Sampling method. Depression was assessed using the Center for Epidemiologic Studies Depression Scale (CES-D). Results A total of 9,554 adolescents participated in the study. The prevalence of depression was 36.6% (95% CI [35.6%–37.6%]); the prevalence of mild and moderate-severe depression was 9.2% (95% CI [8.9%–9.5%]) and 27.4% (95% CI [26.9%–27.9%]), respectively. Female gender (OR = 1.235, P < 0.001), senior secondary school grade (OR = 1.513, P < 0.001), sleep duration of <6 h/day (OR = 2.455, P < 0.001), and living in Hubei province (total number of infected cases > 10,000) (OR = 1.245, P = 0.038) were significantly associated with higher risk of depression. Concern about COVID-19 (OR = 0.632, P < 0.001), participating in distance learning (OR = 0.728, P = 0.001), sleep duration of >8 h/day (OR = 0.726, P < 0.001), exercise of >30 min/day, and study duration of ≥4 h/day (OR = 0.835, P < 0.001) were associated with lower risk of depression. Conclusion Depression was common among adolescents in China during the COVID-19 outbreak. Considering the negative impact of depression on daily life and health outcomes, timely screening and appropriate interventions are urgently needed for depressed adolescents during the COVID-19 outbreak.